MODERN TECHNOLOGIES FOR ENSURING SEISMIC SAFETY OF BUILDINGS - Z.A.Abobakirova; S.M.Mirzababaeva (Western European Studies, 2025)
This article explores modern approaches to reducing seismic risk in buildings through innovative engineering and technological solutions. The study analyzes the effectiveness of both active and passive seismic protection systems, as well as the application of smart materials and adaptive structural designs. Particular attention is given to monitoring and control systems that ensure dynamic stability during earthquakes. Based on comparative analysis, the results demonstrate that the use of modern seismic protection methods significantly increases the reliability and durability of buildings in seismically active regions. Prepared within the framework of the applied research project No. FZ-2020100661 entitled “Development of proposals to enhance the seismic resistance of buildings and structures based on theoretical and experimental studies of active seismic protection systems.”
Keywords: seismic protection; risk reduction; building stability; active systems